Intervention logics in global and international poverty reduction schemes for the extreme poor and the most deprived with a focus on wellbeing and health - Gärde, Johan (O Mundo da Saúde, 2017)
This article will treat the intervention logics of three major global and international poverty reduction programs with a focus on wellbeing and health. The analytical framework of the Millennium Development Goals, the Sustainable Development Goals and the EU Fund for European Aid to the Most Deprived were compared using content and discourse analysis with an interpretative and critical approach. A major shift is taking place globally in the view of poverty reduction, with enhanced intervention logics which are complex as the targets and indicators are formulated by different stakeholders in both developed and developing contexts during diverse time-spans and a variety of priorities, which might not converge in core-dimensions, such as wellbeing, health and social protection. A more interdisciplinary and holistic view is now part of frameworks such as the Sustainable Development Goals, emphasizing environmental and eco-system dimensions in addition to traditional human development dimensions, like income, health, and education, where the impact also should be able to be measured, understood and valued in the interplay of environmental, economic and social determinants affecting wealth, welfare and ultimately, the health and wellbeing of persons and communities. International development funding is now not only restricted to development cooperation to the least developed countries, but middle development countries in Europe and other places, can now also access these aid funds. In addition, to reach out to the most deprived, welfare spending from developed nations are increasingly being allocated to international poverty reduction schemes through regional agendas, like the Europe Strategy 2020. The risk is that too many schemes and policies are not converging in the intervention logics. Another challenge is related to indicators and the resource allocation mainly emphasizing long-term and environmental concerns, such as eco-systems on the macro-level, which might affect short-and medium terms efforts to address human and humanitarian needs and essential health services for the extreme poor and the most deprived, wherever they are, as the geography of the poor is changing.